Analisis Semiotika Pesan Moral pada Film Free Guy - Burhan Fauzan; Ferry Darmawan (Bandung Conference Series: Communication Management, 2024)
Abstract. As mass media, film is a means of education which contains the moral values of society. Films also function as conveying moral messages, information, history and solutions to problems developing in society. This research aims to reveal the moral message contained in the film Free Guy thoroughly and in depth. This research uses a qualitative research method with John Fiske's semiotic analysis approach. This type of research aims to determine the television codes of each scene that contains a moral message in the film Free Guy. Then the data was analyzed using The Codes of Television theory from John Fiske's theory. From the results of this research, it was found that the moral message was (1) solving a problem without using violence (2) respecting other people regardless of role and status (3) courage to fight against injustice. justice (4) understanding oneself for personal gain (5) helping others without asking for reward and having the courage to admit a mistake and also learn to correct it.Keywords: Semiotic Analysis, Film, Free Guy, Moral Message, Mass Communication, John Fiske, The Codes of Television. Abstrak. Sebagai media massa, film menjadi sarana edukasi yang didalamnya mengandung nilai-nilai moral masyarakat. Film juga berfungsi sebagai penyampaian pesan moral, informasi, sejarah maupun solusi atas hal-hal yang bekermbang dimasyarakat. Penelitian ini bertujuan untuk mengungkap pesan moral yang terkandung dalam film Free Guy secara menyeluruh dan mendalam. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan analisis semiotika John Fiske, jenis penelitian ini bertujuan untuk mengetahui kode-kode televisi dari setiap scene yang mengandung pesan moral pada film Free Guy. Kemudian data tersebut dianalisis dengan teori The Codes of Televisian dari teori John Fiske. Dari hasil penelitian ini di temukan pesan moral (1) menyelesaikan suatu masalah tanpa menggunakan kekerasan (2) menghormati orang lain terlepas dari peran serta status (3) keberanian untuk melawan ketidak adilan (4) memahami diri sendiri demi kepentingan pribadi (5) menolong orang lain tanpa meminta imbalan dan berani mengakui sebuah kesalan juga belajar memperbaikinya.